Liverpool [videorecording (DVD)] - Alonso, Lisandro; Alonso, Lisandro; Fernandez, Juan; Irrazábal, Giselle; Cabrera, Nieves (Kino International, 2008)
In the middle of the Atlantic Ocean, Farrel asks the captain of the freighter he works on to go ashore once they reach the port of Ushuaia, a town in southern Argentina. He wants to return to his birthplace and see if his mother is still alive. For the past twenty years he has worked as a seaman. Having reached the cluster of houses where he grew up, Farrel discovers his mother is indeed still alive, but someone else has become part of the family.